Strengthening the financial security of Ukraine's critical infrastructure enterprises under martial law (Economics and region, 2025)
The article examines the financial security of Ukraine’s critical infrastructure enterprises under conditions of full-scale war and intensified global economic instability. The strategic role of financial security as an integral component of enterprise economic stability is substantiated. The interdependence between the level of financial security and liquidity, solvency, financial stability, and financial independence is theoretically justified. The study systematizes key groups of risks affecting financial security – military, financial and economic, and natural-technogenic – and reveals their impact on enterprises’ financial performance. A “risk → indicator → response instrument” matrix is developed to enable systematic identification of financial security threats by linking specific risk categories with measurable financial indicators and appropriate response tools. Based on the analysis of contemporary approaches, a conceptual model grounded in a risk-oriented framework is proposed, integrating financial management instruments with state support mechanisms. The model emphasizes continuous monitoring of key financial indicators, scenario analysis, and regulatory instruments to mitigate financial threats and ensure the continuity and long-term resilience of critical infrastructure enterprises during wartime and post-war recovery.
Keywords: financial security; critical infrastructure enterprises; financial stability; liquidity; solvency; martial law; risk-oriented management; state support